2016
DOI: 10.5539/ijbm.v11n5p146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Occupational Health and Safety Practices on Organizational Commitment, Work Alienation, and Job Performance: Using the PLS-SEM Approach

Abstract: Recent occupational accidents urged enterprises to put more importance on occupational health and safety practices. The pressure by both the public authority and the business and social milieu has played an important role in it. The present study investigated occupational health and safety (OHS) practices in five dimensions, i.e. safety procedures and risk management, safety and health rules, first aid support and training, occupational accident prevention, and organizational safety support. A survey form was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
73
0
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 81 publications
(109 reference statements)
11
73
0
22
Order By: Relevance
“…The study showed that workplace loneliness had a negative effect on job performance and work alienation led to an increase in this effect. These results are consistent with previous research (Gozukara et al, ; Kartal, ; Kaynak, Toklu, Elci, & Toklu, ; Ozcelik & Barsade, ; Shantz, Alfes, Bailey, & Soane, ; Toklu, ; Tummers & Den Dulk, ). These previous studies reported correlations between work alienation and job performance, workplace loneliness and job performance, and work alienation and workplace loneliness.…”
Section: Discussionsupporting
confidence: 93%
“…The study showed that workplace loneliness had a negative effect on job performance and work alienation led to an increase in this effect. These results are consistent with previous research (Gozukara et al, ; Kartal, ; Kaynak, Toklu, Elci, & Toklu, ; Ozcelik & Barsade, ; Shantz, Alfes, Bailey, & Soane, ; Toklu, ; Tummers & Den Dulk, ). These previous studies reported correlations between work alienation and job performance, workplace loneliness and job performance, and work alienation and workplace loneliness.…”
Section: Discussionsupporting
confidence: 93%
“…The results were influenced indirectly through the path of lifestyle variables on the performance of hospital personnel with the results which were not large enough to support the efforts to improve the performance of hospital personnel in the hospital and so that it can be said that the work environment needed not to be of major concern by hospital management to produce performance. These results were consistent with the research of Kaynak (2016) which stated that the safety procedures, organizational support, and other supporting regulations had an effect on the individual performance (Kaynak et al, 2016). Meanwhile, other studies said that variables of work environment were important to contribute toward the rising of performance such as the study that was done by Chandra and Priyono (Chandra & Priyono, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…Work conditions related to performance, is organizational support such as safety procedures, and other supporting regulations (Kaynak, Toklu, Elci, & Toklu, 2016). The hospital work environment can influence the lifestyle behavior of hospital personnel; this in turn will also affect their performance.…”
Section: Introductionmentioning
confidence: 99%
“…Again, the more the job risks the more is the safety and health issues that may occur if the policies and programs are not appropriately maintained [42,43]. On the other hand, job pressure arises from workplace with excessive work, poor work timing and low working culture [44]. Job pressure may also occur from bullying, and bad organizational culture [28].…”
Section: Job Risks and Pressurementioning
confidence: 99%
“…In many cases it was found that employees were not satisfied with the job culture due to too much pressure from work and poor job satisfaction. Thus leading to various mental and psychological breakdowns which are also risks and determine the level of occupational safety [28,44].…”
Section: Job Risks and Pressurementioning
confidence: 99%